A new asterocherid genus (Copepoda: Siphonostomatoida) associated with Callyspongia Duchassaing & Michelotti and reassessment of six species of Asterocheres Boeck - Canário, Roberta; Rocha, Carlos Eduardo Falavigna Da; Neves, Elizabeth; Johnsson, Rodrigo (Zootaxa, 2017)
The family Asterocheridae Giesbrecht has several genera associated with sponges including Asterocheres Boeck, 1859. The type genus is commonly found in sponges but it is also recorded in echinoderms, bryozoans, and corals. A revision of the diagnosis of Asterocheres conducted in 2010 was the beginning of a reorganization process, culminating in the present status of 63 valid species. This study describes a new species and genus of the Asterocheridae. Neoasterocheres gen. nov. shares many characteristics with Asterocheres sensu stricto, except for the antennule segmentation which shows ancestral segments IX–XII fused to segment XIII. The new species of Neoasterocheres gen. nov. was found in association with the sponge Callyspongia sp. sampled at the Yatch Club Bay, located in Todos-os-Santos Bay, Salvador city, Bahia State, Brazil. A revision of the Asterocheres sensu stricto indicates that A. enewetakensis Humes, 1997, A. dysideae Humes, 1996b, A. humesi Varela, 2012, A. rotundus Malt, 1991, A. scutatus Stock, 1966, and A. serrulatus (Humes, 1996a) share this fusion and therefore should be transferred to the new genus. A redescription of Neoasterocheres serrulatus n. comb. is also provided, based on the examination of type specimens.